Impact of blood pressure lowering, cholesterol lowering and their combination in Asians and non-Asians in those without cardiovascular disease: an analysis of the HOPE 3 study. (May 2019) - Pais, Prem; Jung, Hyejung; Dans, Antonio; Zhu, Jun; Liu, Lisheng; Kamath, Deepak; Bosch, Jackie; Lonn, Eva; Yusuf, Salim
Background and design: There are limited data on the effects of blood pressure and cholesterol lowering in Asians at intermediate risk and no cardiovascular disease. We report an analysis of the effects of blood pressure and cholesterol lowering in Asians enrolled in the Heart Outcomes Prevention Evaluation 3 (HOPE 3) trial. Methods: We randomly assigned 6241 Asians and 6464 non-Asians at intermediate risk without cardiovascular disease to candesartan 16 mg/hydrochlorothiazide 12.5 mg or placebo and rosuvastatin 10 mg or placebo. The first co-primary outcome was a composite of cardiovascular disease death, myocardial infarction and stroke. The second co-primary outcome additionally included heart failure, cardiac arrest and revascularisation. Median follow-up was 5.6 years. Results: Reduction in systolic blood pressure was less among Asians (4.3 vs. 7.7 mmHg for non-Asians, P < 0.0001) mainly due to a lesser effect in Chinese (2.1 mmHg) than in other Asians (7.3 mmHg), reduction in the latter being similar to non-Asians. The effect on the composite outcomes was similar, with no significant benefits from blood pressure lowering for either Asians (Chinese or non-Chinese) or non-Asians. Rosuvastatin reduced low-density lipoprotein cholesterol to a lesser degree in Asians (0.49 mmol/L (–19.1 mg/dL) compared with non-Asians 0.95 mmol/L (−36.7 mg/dL), P interaction < 0.0004). Yet both groups had similar reductions in the two co-primary outcomes. There was no increase in permanent medication discontinuation due to muscle-related symptoms in either group. There was an excess in new diabetes in non-Asians (4.70% rosuvastatin, 3.52% placebo, P = 0.025) but not in Asians (3.02% rosuvastatin, 4.04% placebo, P = 0.0342), P interaction = 0021. Conclusions: Candesartan/hydrochlorothiazide had fewer effects in reducing blood pressure in Chinese and rosuvastatin reduced low-density lipoprotein cholesterol to a lesser extent in Asians compared with non-Asians. There was no overall reduction in clinical events with lowering blood pressure in either Asians or non-Asians, whereas there were clear and consistent benefits with lipid lowering in both. Despite extensive analyses, we have no obvious explanation for the observed findings. Future studies need to include larger numbers of individuals from different regions of the world to ensure that the results of trials are applicable globally.